Nitrogen-fixing Rhizobium-legume symbiosis: are polyploidy and host peptide-governed symbiont differentiation general principles of endosymbiosis? - Maróti, Gergely; Kondorosi, Éva (Frontiers in Microbiology, 2014)
The symbiosis between rhizobia soil bacteria and legumes is facultative and initiated by nitrogen starvation of the host plant. Exchange of signal molecules between the partners leads to the formation of root nodules where bacteria are converted to nitrogen-fixing bacteroids. In this mutualistic symbiosis, the bacteria provide nitrogen sources for plant growth in return for photosynthates from the host. Depending on the host plant the symbiotic fate of bacteria can either be reversible or irreversible. In Medicago plants the bacteria undergo a host-directed multistep differentiation process culminating in the formation of elongated and branched polyploid bacteria with definitive loss of cell division ability. The plant factors are nodule-specific symbiotic peptides. About 500 of them are cysteine-rich NCR peptides produced in the infected plant cells. NCRs are targeted to the endosymbionts and the concerted action of different sets of peptides governs different stages of endosymbiont maturation. This review focuses on symbiotic plant cell development and terminal bacteroid differentiation and demonstrates the crucial roles of symbiotic peptides by showing an example of multi-target mechanism exerted by one of these symbiotic peptides.